Sistem Informasi Pemesanan Lapangan Futsal Berbasis Web dengan Integrasi Payment Gateway Menggunakan Model Waterfall - Yuliana (CV. Multi Kreasi Media, 2026)
The rapid development of information technology encourages business actors to utilize web-based information systems to improve efficiency and service quality. Currently, Neo S Futsal Court still applies a manual booking process, which may lead to recording errors, limited access to schedule information, and inefficiencies in the payment process. This study aims to design and develop a web-based futsal court booking information system integrated with a payment gateway to facilitate the booking process and online payment transactions. The system development method used is the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The developed system provides features such as court booking, schedule management, automatic payment confirmation, and transaction reports. The results show that the proposed information system is able to improve the effectiveness and efficiency of the futsal court booking process, minimize recording errors, and provide convenience for both customers and administrators in conducting transactions and managing data.